(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
Reformation of the health care system of Ukraine has become urgent and socially relevant. A scientifically grounded change in the organization of provision of medical services in rural areas will provide an opportunity to receive qualitative and timely diagnostics for local residents. Carrying out high-quality medical examination in rural areas, timely detection of diseases, especially genetic in the early stages, systemic supervision of certain groups of patients, carrying out of preventive and sanitary measures will allow to effectively carry out medical process.